Advances in Management Engineering - Hernández, Cesáreo (Lecture Notes in Management and Industrial Engineering,, 2017)
This book deals with research in open challenges in Management Engineering in the 21st century, as well as selected opportunities and solutions to remedy them. Management Engineering is an emerging field that extends the analytical methods used in traditional Industrial Engineering and Industrial Organization to address the economic, behavioral and social dimensions of companies and their environments. Management Engineering extends its domain beyond the firm and the market to encompass the modeling and policy design of physical landscapes populated by social agents. The developments of the 21st century have made it necessary to adopt an integrative and global view of the different methodologies and tools that facilitate managers' decision-making processes, ranging from the strategic to the operational level. This book equips readers with precisely these urgently needed resources.